2015
DOI: 10.1016/j.bbi.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sleep deprivation and circadian misalignment on cortisol, inflammatory markers, and cytokine balance

Abstract: Cortisol and inflammatory proteins are released into the blood in response to stressors and chronic elevations of blood cortisol and inflammatory proteins may contribute to ongoing disease processes and could be useful biomarkers of disease. How chronic circadian misalignment influences cortisol and inflammatory proteins, however, is largely unknown and this was the focus of the current study. Specifically, we examined the influence of weeks of chronic circadian misalignment on cortisol, stress ratings, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
256
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(273 citation statements)
references
References 89 publications
15
256
1
1
Order By: Relevance
“…Short sleep duration is correlated to an increased risk of adult overweight/obesity and some studies claim this to be related to a reduced circulating leptin level relative to what is predicted by fat mass [93], whereas others have found increased circulating leptin levels after a period of short sleep [36]. It should be noted, however, that experimental studies are far from consistent where it concerns the metabolic consequences of short sleep duration [94][95][96]. Shift work has been found to be associated with unfavourable dietary habits and consequently to overweight and related chronic diseases such as coronary heart disease, metabolic syndrome and type 2 diabetes [97].…”
Section: Chronic Somatic Health Effectsmentioning
confidence: 84%
“…Short sleep duration is correlated to an increased risk of adult overweight/obesity and some studies claim this to be related to a reduced circulating leptin level relative to what is predicted by fat mass [93], whereas others have found increased circulating leptin levels after a period of short sleep [36]. It should be noted, however, that experimental studies are far from consistent where it concerns the metabolic consequences of short sleep duration [94][95][96]. Shift work has been found to be associated with unfavourable dietary habits and consequently to overweight and related chronic diseases such as coronary heart disease, metabolic syndrome and type 2 diabetes [97].…”
Section: Chronic Somatic Health Effectsmentioning
confidence: 84%
“…This finding is in accordance with the increase in CRP levels we observed as a result of 3 d of circadian misalignment. Wright et al (20) reported that weeks of gradual changes in circadian alignment (induced by 24.6-h behavioral cycles under dim light) increased CRP as well as TNF-α and IL-10 (antiinflammatory) levels in humans. However, shift workers typically undergo rapid, large shifts of their behavioral and light/dark cycles relative to their internal body clock, as occurred in our study.…”
Section: Possible Mechanisms Involved In Circadian Misalignment-mediatedmentioning
confidence: 99%
“…The first study demonstrated that 8 d of sleep restriction combined with multiple days of circadian misalignment increased C-reactive protein (CRP) levels-a marker of systemic inflammation (19). The second study demonstrated that weeks of gradual changes in circadian misalignment (induced by 24.6-h behavioral cycles in dim light) increased CRP, tumor necrosis factor (TNF)-α (proinflammatory) and interleukin (IL)-10 (antiinflammatory) levels (20). The relevance of the findings of the latter study to shift workers is unclear, considering that shift workers are not kept in dim light conditions (night workers have been reported to be exposed to ∼50-300 lx during night shifts and natural environmental illumination of varying strength) and typically undergo rapid and large shifts of their behavioral/environmental cycles relative to their internal circadian system-that is, due to the inertia of the internal circadian system, the timing of the circadian system cannot quickly adjust to large and rapid shifts in behavioral/environmental cycles (21).…”
mentioning
confidence: 99%
“…In modern industrialized societies, where the solar day and the endogenous circadian clock are no longer synchronized, negative effects of chronic circadian misalignment appear, such as reduction in cortisol levels and increase in both inflammatory and anti-inflammatory serum cytokines production in baseline conditions [23]. In mice, circadian disruption by changing light and dark phases from 12 h to 10 h, led to complex alterations of the immune response to experimental endotoxemia both in the brain and in the periphery (e.g., blunted response in the periphery and hippocampus and an exaggerated response in hypothalamic IL-6 and TNF-a expression) [24 ].…”
Section: Sleep and Immunitymentioning
confidence: 99%